Representasi Visual Budaya Kolombia Pada Film Animasi “Encanto” - Indah Putri Ani; Jupriani Jupriani (Universitas Katolik Widya Karya Malang, 2023)
This study analyzes the system of signs and meanings of Colombian culture in the animated film